PERTENTANGAN NORMA DALAM PENGATURAN PENDAFTARAN DAN PENDIRIAN COMMANDITAIRE VENNOOTSCHAP (CV) - Maharni Partyani, Ketut Caturyani (Institut Hindu Dharma Negeri Denpasar, 2019)
Registration and establishment of CV in Indonesia occurs in norms of conflict, both of which are regulated in Article 23 of the Criminal Procedure Code with Article 3 of the Minister of Law and Human Rights concerning ‘Application for CV registration. KUHD through clerks in the district court while Regulation of the Minister of Law and Human Rights by the Minister of Law and Human Rights through SABU (Business Administration System). The provisions of the Criminal Procedure Code have never been revoked or declared invalid. This study offers a way out in registering CV establishments conducted at the two institutions designated in the legislation, namely in accordance with the provisions of article 23 KUHD at the District Court Registrar Office where the CV is located and in accordance with Article 3 of Regulation of the Minister of Law and Human Rights Number 17 Year 2018 registered with the Ministry Law and Human Rights through the Business Entity Administration System (SABU) online.